Distributive justice and access to advantage : G.A. Cohen's egalitarianism - Kaufman, Alexander, 1958- (Cambridge, United Kingdom : Cambridge University Press, 2014)
"G. A. Cohen was one of the world's leading political theorists. He was noted, in particular, for his contributions to the literature of egalitarian justice. Cohen's classic writings offer one of the most influential responses to the currency of the egalitarian justice question - the question, that is, of whether egalitarians should seek to equalize welfare, resources, opportunity, or some other indicator of well-being. Underlying Cohen's argument is the intuition that the purpose of egalitarianism is to eliminate disadvantage for which it is inappropriate to hold the person responsible. His argument therefore focuses on the appropriate role of considerations regarding responsibility in egalitarian judgment. This volume comprises chapters by major scholars addressing and responding both to Cohen's account of the currency of egalitarian justice and its practical implications and to Cohen's arguments regarding the appropriate form of justificatory arguments about justice"--
Machine generated contents note: Introduction Alexander Kaufman; Part I. Justice and Justification: 1. The fundamental disagreement between luck egalitarians and relational egalitarians Elizabeth Anderson; 2. Justice, interpersonal morality, and luck egalitarianism Peter Vallentyne; 3. The egalitarian ethos as a social mechanism Joseph H. Carens; 4. Justice and the crooked wood of human nature Adam Cureton; 5. Facts, principles, and the third man Lea Ypi; Part II. Justice and Equality: 6. Equality and freedom: Cohen's critique of Sen Alexander Kaufman; 7. The incoherence of luck egalitarianism David Miller; 8. What is the point of egalitarian social relationships? Patrick Tomlin; 9. Basic equality and the currency of egalitarian justice Gabriel Wollner; Part III. Equality and Society: 10. Why not capitalism? Richard J. Arneson; 11. The labor theory of justice Chandran Kukathas; 12. Rescuing justice and equality from libertarianism Serena Olsaretti.
Print version record.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Cohen, G. A. -- 1941-2009.; Cohen, G. A. -- 1941-2009; Distributive justice; Equality; Justice distributive; POLITICAL SCIENCE -- History & Theory; POLITICAL SCIENCE -- Essays; POLITICAL SCIENCE -- Government -- General; POLITICAL SCIENCE -- Government -- National; POLITICAL SCIENCE -- Reference; Distributive justice; Equality